2017
DOI: 10.2298/fuee1701137k
|View full text |Cite
|
Sign up to set email alerts
|

Modified internal model control for a therapeutic robot

Abstract: We present the use of the modified internal model controller (MIMC) and the ?Probability Tube? (PT) action representation for robot-assisted upper extremities training of hemiplegic patients. The robot-assisted training session has two phases. During the first "demonstration" phase the robot learns from the therapist the target path through examples. In the second "exercise" phase the robot assists a patient to follow the target path. During this process, the control limits the interface forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…And the results showed that it further improved the system accuracy. The work in (Kostić M D et al, 2016) applied the modified internal model method to rehabilitation robot. The experiment results indicated that the proposed method did well in positional error between the target and the reached position.…”
Section: Introductionmentioning
confidence: 99%
“…And the results showed that it further improved the system accuracy. The work in (Kostić M D et al, 2016) applied the modified internal model method to rehabilitation robot. The experiment results indicated that the proposed method did well in positional error between the target and the reached position.…”
Section: Introductionmentioning
confidence: 99%